Rāingān phon kānsưksā khrōngkān sưksā rūpb̄æp læ n̄æothāng kānsongs̄œm khwāmkhemkh̄æng kh̨̄ong ʻongkān b̨̄orihān sūan tambon - Orapin Sopchokchai (Mūnnithi Sathāban Wičhai ph̄ưa Kānphatthanā Prathēt Thai, 1997)
Study on measures to improve capability limits in administering development activities of village level administration agencies in Thailand.